THE ROLE OF PSYCHOLINGUISTICS IN EARLY CHILDHOOD LANGUAGE DEVELOPMENT (AGES 1-6) - Siahaan, Indah Peronika; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
The significance of comprehending language development from a young age is covered in this article, along with how a psycholinguistic approach can offer a solid basis for creating English language instruction that works for kids at this critical juncture in life. This article uses a psycholinguistic method to analyze the literature and trace empirical investigations of language development in early life. The purpose of this method to English language learning at this crucial developmental stage was investigated through data analysis. This means that incorporating psycholinguistic methods into early English instruction for kids has a lot of promise to help them develop their language skills. Teachers can foster a relevant and encouraging learning environment for kids by comprehending and putting psycholinguistic ideas into practice. Language development in early childhood is a critical aspect of human growth, particularly between the ages of 1-6, when children undergo rapid linguistic advancements. Psycholinguistics provides valuable insights into how children acquire, understand, and use language, combining cognitive psychology and linguistics to explore the brain mechanisms underlying language processing. This paper examines the major theories of language acquisition, cognitive and social influences on development, and the role of environmental factors. By integrating psycholinguistic principles with research findings, this article highlights how early childhood educators and caregivers can enhance language development. The article concludes with recommendations for future research directions to further explore bilingualism, technology's impact on language acquisition, and interventions for language disorders.